Tinjauan Yuridis Atas Keabsahan Perjanjian Jual Beli dalam Kasus Order Fiktif pada Layanan Pesan Antar Makanan - Emir Adzan Syazali; Fikri Azim; Alfin Prima Pulungan; Lutfi Asroni; Agusirawan Agusirawan; Abdul Quddus (Wajah Hukum, 2026)
The widespread practice of fictitious orders in food delivery services that charge payment to the recipient of the order raises legal issues, particularly regarding the validity of the sales and purchase agreements that occur in these transactions. This practice not only harms the recipient of the order, but also has the potential to create legal uncertainty in the relationship between the seller, the orderer, and the service provider. Therefore, a legal study is needed to assess whether the agreements arising in cases of fictitious orders meet the requirements of a valid agreement according to civil law and how the parties who place the order are liable. This study uses a normative legal method with a statutory, conceptual, and case approach. Legal materials were obtained through literature studies and analyzed descriptively-qualitatively. The results of the study indicate that agreements in cases of fictitious orders can be declared invalid or can be canceled due to the failure to fulfill the elements of the agreement, and the orderer can be held liable for any losses incurred.